2018
DOI: 10.1371/journal.pone.0206739
|View full text |Cite
|
Sign up to set email alerts
|

One for all: Mating compatibility among various populations of olive fruit fly (Diptera: Tephritidae) for application of the sterile insect technique

Abstract: The olive fruit fly, Bactrocera oleae (Rossi), is the most important insect pest for the cultivation of olives worldwide. Considerable research efforts have been invested in the past decades to develop eradication or suppression tactics for use within an area-wide integrated pest management (AW-IPM) approach that includes a sterile insect technique (SIT) component. One of the major obstacles encountered in the development of SIT for olive fruit fly was the inferior quality of the mass-reared flies, expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This is in accordance with earlier studies which indicated that massreared tephritid males tend to begin calling and mating earlier in the day than the wild population [28,29]. Mating latency is considered critical for the success of the SIT/RIDL, as earlier matings of wild males would potentially leave fewer opportunities for sterile males to transfer their sterile sperm to the wild females [11]. Additional bioassays in larger field cages and under natural light conditions are required to further explore differences in mating latency between AR and W flies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with earlier studies which indicated that massreared tephritid males tend to begin calling and mating earlier in the day than the wild population [28,29]. Mating latency is considered critical for the success of the SIT/RIDL, as earlier matings of wild males would potentially leave fewer opportunities for sterile males to transfer their sterile sperm to the wild females [11]. Additional bioassays in larger field cages and under natural light conditions are required to further explore differences in mating latency between AR and W flies.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the mating behavior of olive fruit flies have indicated that colonization and rearing under laboratory conditions for many generations have a negative effect on male fitness and mating behavior [9,10]. Generally, long-term rearing under artificial conditions negatively affects behavioral and physiological aspects of insects [11], in addition to their longevity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing tsetse mating behavior under field conditions is challenging and expensive, and the results can be influenced by several environmental, climatic and ecological parameters which cannot be controlled. Walk-in field cages have been utilized successfully as a surrogate for field studies to conduct mating compatibility, mating competitiveness and other behavioral studies with fruit flies [ 104 ], lepidoptera [ 105 ], mosquitos [ 106 ] and tsetse flies [ 89 ].…”
Section: Main Research Achievements—livestock Pestsmentioning
confidence: 99%
“…Non-insecticidal alternatives that have worked in some situations or shown potential include (a) mass trapping programs [84,85,86], (b) sterile insect technique (SIT) [87,88,89], (c) particle film [90,91,92] and (d) biological control using natural enemies [66]. Symbiosis-based strategies are still under developed, albeit attempts with the use of copper products as symbionticides [92,93,94].…”
Section: The Iconic Mediterranean Crop Olives and Its Main Insect mentioning
confidence: 99%